GAVIN: Gene-Aware Variant INterpretation for medical sequencing. Issue 1 (December 2017) - van der Velde, K.; de Boer, Eddy; van Diemen, Cleo; Sikkema-Raddatz, Birgit; Abbott, Kristin; Knopperts, Alain; Franke, Lude; Sijmons, Rolf; de Koning, Tom; Wijmenga, Cisca; Sinke, Richard; Swertz, Morris
Abstract We present Gene-Aware Variant INterpretation (GAVIN), a new method that accurately classifies variants for clinical diagnostic purposes. Classifications are based on gene-specific calibrations of allele frequencies from the ExAC database, likely variant impact using SnpEff, and estimated deleteriousness based on CADD scores for >3000 genes. In a benchmark on 18 clinical gene sets, we achieve a sensitivity of 91.4% and a specificity of 76.9%. This accuracy is unmatched by 12 other tools. We provide GAVIN as an online MOLGENIS service to annotate VCF files and as an open source executable for use in bioinformatic pipelines. It can be found athttp://molgenis.org/gavin .